EDITORIAL - Sewpaul, Vishanthie (Social Work/Maatskaplike Werk, 2014)
The provision of comprehensive social services and programmes that empower vulnerable people in the fields of substance abuse, HIV and AIDS, as well as people with special needs such as migrants, remains a challenge to Social Work. In this edition, two articles look at complex phenomena such as migration and human trafficking: one presents a framework for understanding risk and protective factors relevant to migrants and offers guidelines for social work intervention; the other explores the role the social worker in human trafficking and the place of social work as a profession vis-à-vis this phenomenon